Implementing virtual reality training in policing: A case study using the technology acceptance model - Halford, Eric (International journal of police science & management, 2025)
The purpose of this article is to explore the acceptance of virtual reality (VR) training in a single police service that implemented the technology as a key part of its training procedures. We examined satisfaction data from surveys of police officers and civilian staff collected over three years, complemented by interviews with staff involved in the development and use of VR. The technology acceptance model (TAM) provides the theoretical framework for exploring six hypotheses based on previous research, enabling the study to assess the perceived ease of use, usefulness, enjoyment, immersion, interaction, and future intention to use VR technology. Insights were derived from a combination of descriptive and inferential statistics, along with thematic analysis. Results show a consistent upward trend in officer satisfaction with VR, along with strong evidence of perceived usefulness, immersion, and interactivity. Significant findings indicate a link between satisfaction with VR and education, with PhD holders reporting the highest levels of satisfaction. Gender differences were also evident, with female participants expressing higher satisfaction than males. In addition, participants with more than 10 years of service reported significantly lower satisfaction than mid-service officers, suggesting that age may be a contributory factor. These findings are discussed in the context of the interplay between demographic factors and technology acceptance in policing. We emphasize the need for the development of tailored training and communication strategies to support the effective implementation of VR technology as a medium for instruction for employees of all ages and genders.